2023
DOI: 10.1002/art.42406
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase of Circulating Transitional B Cells and Autoantibodies to Joint‐Related Proteins in Patients With Metastatic Melanoma Developing Checkpoint Inhibitor–Induced Inflammatory Arthritis

Abstract: Objective To investigate potential associations between B cell–related immunologic changes and development of inflammatory arthritis (IA) after treatment with immune checkpoint inhibitors (ICIs). Methods Patients who developed ICI‐induced IA (ICI‐IA) and patients who did not develop immune‐related adverse events (non‐IRAE) after receiving ICIs to treat metastatic melanoma were consecutively recruited. Blood samples were collected at the time of ICI‐IA occurrence and at different time points during treatment. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cappelli et al (40) showed that more than 11% of patients with seronegative ICI-induced arthritis had anti-RA33 antibodies, whereas none of the patients not developing arthritis had these antibodies. Similarly, a significant increase in transitional B cells and specific autoantibodies to joint-related proteins was documented in a prospective cohort of patients treated with ICI for melanoma who developed inflammatory arthritis (41). Altogether, these finding point at an autoimmune contribution to disease pathogenesis also in a set of conditions traditionally considered seronegative.…”
Section: Novel Antibodiesmentioning
confidence: 71%
“…Cappelli et al (40) showed that more than 11% of patients with seronegative ICI-induced arthritis had anti-RA33 antibodies, whereas none of the patients not developing arthritis had these antibodies. Similarly, a significant increase in transitional B cells and specific autoantibodies to joint-related proteins was documented in a prospective cohort of patients treated with ICI for melanoma who developed inflammatory arthritis (41). Altogether, these finding point at an autoimmune contribution to disease pathogenesis also in a set of conditions traditionally considered seronegative.…”
Section: Novel Antibodiesmentioning
confidence: 71%
“…According to previous studies, ICI-induced arthritis has been observed in around 5% of patients treated with ICIs, exhibiting varying degrees of severity (Weinmann and pisetsky, 2019;Gatto et al, 2022). Some studies have suggested a higher incidence of arthritis with pembrolizumab (Xu et al, 2018;Ramos-Casals et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Das et al 47 observed a reduction in circulating B cells in patients with melanoma after ICI therapy and that this was associated with greater risk of ICI‐induced irAEs as well as irAE severity. More recently, Gatto et al 48 reported that the frequency of transitional B cells is higher in patients that develop ICI‐induced arthritis compared to those who do not. Collectively, these studies indicate that the induction of irAEs may be seen in individuals who already have a break in B‐cell tolerance as demonstrated by pre‐treatment autoantibodies, but that ICI therapy may also promote loss of B cell tolerance, potentially through the promotion of the Tfh‐B cell axis, resulting in autoantibodies that contribute to disease or are evidence of the evolution of autoreactivity due to ICI therapy.…”
Section: Ici‐induced Iraesmentioning
confidence: 99%